Axiomatic Design Approach for Nonlinear Multiple Objective Optimizaton Problem and Robustness in Spring Design - FEYZİOĞLU, AHMET (INST INFORMATION & COMMUNICATION TECHNOLOGIES-BULGARIAN ACAD SCIENCES, 2017)
This paper gives general information about multi-objective, axiomatic and robust design approaches and considers a solution model of nonlinear multi objective optimization problem based on applying a new robust design approach. Both axiomatic and robust design approaches were used complementarily in a case study with distinct multi-objectives. In this case study, the main target was achieving each objective optimum to minimize the mass and the shear stress of a spring by integrating robustness and durability at the design stage due to trade off between objectives. This spring problem was examined using the independence axiom of the axiomatic design methodology. Also, semangularity and reangularity concepts were used and design matrices were formed to find coupled and decoupled solutions. It was observed that there were some acceptable design parameter values for which the design became decoupled. Graphical and numerical results were checked to see if they were compatible with each other. Finally, this decoupled design was given appropriate tolerances by using robust design method. This way, a robust and durable spring was designed which would satisfy the given specifications with minimum cost in the existing literature from the view point of axiomatic design approach.
Keywords: Axiomatic design; multi-objective design; robustness.